Relay cross metathesis reactions of vinylphosphonates - Malla, Raj K.; Ridenour, Jeremy N.; Spilling, Christopher D. (Beilstein Journal of Organic Chemistry, 2014)
Dimethyl (β-substituted) vinylphosphonates do not readily undergo cross metathesis reactions with Grubbs catalyst and terminal alkenes. However, the corresponding mono- or diallyl vinylphosphonate esters undergo facile cross metathesis reactions. The improved reactivity is attributed to a relay step in the cross metathesis reaction mechanism.
Keywords: centrolobine; metathesis; organo phosphorus; relay; vinyl phosphonate